Method for preparing porous material based on graphite tailings
By pretreating graphite tailings and alkali melting treatment, porous materials with high specific surface area were prepared, which solved the problem of low specific surface area of porous materials in the prior art, and significantly improved their adsorption performance and environmental restoration capabilities.
Patent Information
- Application Number
- CN202411559608.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
AI Technical Summary
The specific surface area of porous materials prepared by tailings in the prior art is not high, which limits its performance and range in applications such as adsorption and catalysis.
By pretreating the graphite tailings and melting the alkali, aged, crystallized and dried in turn, graphite tailings porous materials with high specific surface area and good pore structure were prepared.
The specific surface area of porous materials has been achieved to reach more than 374.3m2/g, which significantly improves its adsorption performance, can effectively remove pollutants in water and soil, and show excellent performance in environmental restoration.
Smart Images

Figure CN119455891A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of environmentally friendly treatment of solid waste, and more specifically, to a method for preparing porous materials based on graphite tailings. Background Art
[0002] Porous materials are materials with a large number of pores, usually with the following characteristics: low relative density, high specific strength, high specific surface area, good sound and heat insulation, good permeability. Due to the characteristics of porous materials, they are widely used. With high specific surface area and porous structure, porous materials can effectively adsorb and separate target substances and are used in water treatment, gas separation and other fields. They can also be used in catalyst carriers, sensors, energy storage, filtration and protection.
[0003] For environmental protection reasons, tailings, which are prone to dust and dam breaches and have obvious land accumulation problems, are considered as ideal raw materials for preparing porous materials. The technical solutions for preparing porous materials using tailings as raw materials in the prior art include:
[0004] (1) The Chinese invention patent with publication number CN105693277A discloses a porous material of iron tailings used as a microbial ceramsite filter material, and its preparation method and application. The material includes a porous material of iron tailings and microorganisms loaded on the porous material; the raw material composition and mass percentage of the porous material are as follows: iron tailings: 65-85%; clay: 6-19%; pore-forming agent: 4-12%; calcium carbonate: 1-6%. The sum of the mass percentages of each component is 100%. After ball milling, granulation, drying, aging and calcination processes, a porous material of iron tailings used as a microbial ceramsite filter material is obtained, and the porosity can reach greater than 40% and the specific surface area is greater than 5.0m 2 / g, crushing force is less than 0.8kN.
[0005] (2) The Chinese invention patent with publication number CN103896534A discloses a method for preparing porous materials using rare earth tailings, which comprises mixing rare earth tailings and cement in a mass ratio of 2-4:8-6, adding lithium carbonate, starch and potassium permanganate, adding H2O2 after stirring, and curing for 20-30 hours under static conditions. The chemical composition of the rare earth tailings is utilized to replace part of the cement, and the basic raw materials are debugged by adding additives, adjusting the proportion of raw materials, additives, stimulants and foaming agents, and strictly controlling each link of the preparation process so that the foaming speed matches the coagulation time of the matrix, thereby preparing a low-density and high-strength rare earth-containing porous material with a pore size of less than 1 mm and uniform bubble distribution. According to the test results of the embodiment of the patent, the specific surface areas are 28.48 m 2 / g, 7.37m 2 / g and 20.03m 2 / g.
[0006] It can be seen that a variety of technical solutions for preparing porous materials using tailings have been proposed in the prior art. However, the specific surface area of the porous materials prepared according to these solutions is not high. In the applications of porous materials such as adsorption and catalysis, the specific surface area is an important beneficial property. A high specific surface area means that the material has more active sites, which enables them to adsorb more gas or liquid molecules, which is particularly important for applications such as gas storage, separation and purification. In catalytic applications, more active sites increase the chances of reactant molecules contacting the catalyst, improving the reaction rate and efficiency. Therefore, in order to improve the application performance and application range of porous materials, a porous material with a higher specific surface area is needed. Summary of the invention
[0007] To solve the above problems, the technical solution adopted in this application is a method for preparing porous materials based on graphite tailings; the graphite tailings are pretreated and alkali-melted, and then aged, crystallized and dried in sequence to obtain a porous graphite tailings material.
[0008] Optionally, the pretreatment includes grinding and screening the graphite tailings raw material for the first time, and then drying it for the first time, mixing the dried product with hydrochloric acid, placing it in a reactor for pickling and impurity removal treatment, centrifuging the pickled sample, washing it with distilled water until the pH is neutral, centrifuging it again, drying the separated sample for a second time, and grinding and screening it for a second time for use.
[0009] Optionally, the alkali melting treatment includes uniformly mixing the pretreated graphite tailings, sodium hydroxide and aluminum hydroxide, placing the mixture in a high-temperature sintering furnace for calcining, and grinding the calcined sample to obtain alkali-melted clinker.
[0010] Optionally, aging includes mixing deionized water with the alkali-molten clinker and stirring at room temperature to form a precursor mixture.
[0011] Optionally, the crystallization includes transferring the precursor mixture into a reactor and sealing it for hydrothermal crystallization. After the crystallization is completed, the mixture is cooled to room temperature, and the product is repeatedly washed with deionized water and centrifuged until the pH of the washing water is neutral.
[0012] Optionally, in the pretreatment process, after the first grinding and screening and the second grinding and screening, raw materials with a particle size range of 200 mesh-300 mesh are selected for subsequent treatment, the drying temperature of the first drying and the second drying is 100-105°C, the mass fraction of hydrochloric acid in the pretreatment process is 3%-15%, and the temperature of pickling and impurity removal is 70-85°C.
[0013] Optionally, in the alkali melting treatment process, sodium hydroxide and graphite tailings are mixed in a mass ratio of 0.8-1.5:1, and the calcination temperature of the calcination process is 500-800° C. and the calcination time is 1-2 hours.
[0014] Optionally, in the aging process, deionized water and alkali-molten clinker are mixed in a mass ratio of 4-8:1, the mass ratio of silicon to aluminum in the mixture is 1:1, and the stirring time is 2-12 hours.
[0015] Optionally, the crystallization temperature of the crystallization process is 60-105° C., and the crystallization time is 4-24 h.
[0016] Optionally, the last drying step before obtaining the graphite tailings porous material is performed at a drying temperature of 100-105°C.
[0017] The beneficial effects of the method for preparing porous materials based on graphite tailings provided in this application are:
[0018] Graphite tailings are used to prepare porous materials with high specific surface area and good pore structure. The porous materials have excellent adsorption properties and can effectively remove pollutants in water and soil, such as heavy metal ions, ammonia nitrogen ions, phosphate ions, fluoride ions, etc. The graphite tailings are pretreated and alkali-melted, and then aged, crystallized and dried in sequence to obtain graphite tailings porous materials. The use of graphite tailings to prepare porous materials not only reduces the accumulation of tailings, reduces the pollution of solid waste to the environment, and realizes the efficient utilization of waste resources, but also shows excellent performance in environmental remediation. The specific surface area of the prepared porous material is higher than 370m 2 / g, suitable for water treatment, gas adsorption, soil remediation and other fields, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art.
[0020] Figure 1 XRD patterns of porous materials before and after synthesis;
[0021] Figure 2 is the SEM image of graphite tailings;
[0022] Figure 3 is the SEM image of the porous material;
[0023] Figure 4 FTIR spectra before and after the synthesis of porous materials from graphite tailings;
[0024] Figure 5 This is a diagram showing the effect of removing high concentration ammonia nitrogen. DETAILED DESCRIPTION
[0025] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0026] Example 1
[0027] Pretreatment: Grind and sieve the graphite tailings raw materials for the first time, take the powder of 200-300 mesh sieve segment for use, and then dry it for the first time at a drying temperature of 100°C. Mix the dried powder with 3% hydrochloric acid by mass and place it in a reactor for pickling and impurity removal treatment at a pickling temperature of 70°C for 2 hours. Centrifuge the pickled sample, wash it with distilled water until the pH is neutral, centrifuge it again, dry the separated sample for the second time at a drying temperature of 100°C, grind and sieve it for the second time, and take the powder of 200-300 mesh sieve segment for use.
[0028] Alkali melting treatment: The pretreated graphite tailings and sodium hydroxide solid are mixed and ground evenly in a mass ratio of 0.8:1 of alkali to ore, and aluminum hydroxide is added to adjust the silicon-aluminum ratio to 1:1. The mixture is placed in a high-temperature sintering furnace for calcination at a temperature of 500°C for 1 hour. After completion, the mixture is cooled and ground to obtain alkali-melted clinker.
[0029] Aging: Deionized water and alkali molten clinker were mixed in a ratio of 4:1 and stirred at room temperature for 2 hours to form a precursor mixture.
[0030] Crystallization: The precursor mixture was transferred to a reactor and sealed. Hydrothermal crystallization was performed at 60°C for 4 hours without stirring. The crystallized product was cooled to room temperature, filtered in a filter, and washed with deionized water until neutral.
[0031] Drying: The washed porous material product is dried in a drying oven at a temperature of 100° C. to obtain a graphite tailings synthetic porous material.
[0032] Characterization analysis:
[0033] X-ray diffractometer (XRD): A Rigaku SmartLab (3KW) X-ray diffractometer (XRD) was used for detection. The detection conditions were: Cu target, Kα diffraction source, tube voltage 40 kV, tube current 40 mA, scanning rate 8° / min, and angle range 5°-60° (data were processed using Jade6.5 software).
[0034] like Figure 1 As shown in the figure, the main components of graphite tailings are quartz and biotite. After alkali melting, the diffraction peaks of quartz and biotite in the graphite tailings disappear, and they are converted into sodium silicate and sodium aluminate, the precursors of synthetic zeolites. Through hydrothermal treatment, a porous material with high crystallinity is obtained. Its sharp diffraction peaks and silicon-aluminum ratio close to 1 confirm the successful synthesis of the porous material NaA zeolite.
[0035] Fourier transform infrared spectrometer (FTIR): Thermo Fisher Nicolet 6700 Fourier transform infrared spectrometer (FTIR) was used. The sample and KBr were mixed and ground at a mass ratio of 1:300 and then pressed into tablets. -1 The scan is performed in the wave number range with a resolution of 4 cm -1 , the scanning times were 32 times to eliminate the interference of moisture and CO2 in the air.
[0036] like Figure 4 As shown, Figure 4 This further illustrates the structural change of graphite tailings into porous materials. The peak of NaA zeolite appears at 1001 cm -1 The peak at 20° is the bending vibration of TOT (where T is Al or Si). Compared with graphite tailings, this peak shifts to a lower wave number. This change is attributed to the smaller Si-O-Na bond length and bond angle in zeolite A than in TOS.
[0037] Scanning electron microscope (SEM): The appearance and particle size of the samples were observed using a Japanese Hitachi SU-8010 scanning electron microscope (SEM). Before testing, the samples were evenly dispersed on the conductive glue and gold-sprayed.
[0038] like Figure 2 and Figure 3 As shown in Figure 2, the graphite tailings have been transformed from irregular flakes to regular cubic small particles. This result confirms that the graphite tailings have been successfully transformed into porous materials, which is consistent with the results of XRD and FTIR.
[0039] Brunauer-Emmett-Teller test: Using the fully automatic pore size analyzer (ASAP 2460) from Micromeritics, USA, the N2 adsorption-desorption isotherm test was performed on the sample after vacuum degassing at 350℃ for 8h at 77K with high-purity N2 as the adsorbent.
[0040] Figure 5The effect of the dosage of porous materials on ammonia nitrogen adsorption is shown: in the range of 1g / L to 6g / L, the removal rate of ammonia nitrogen increases rapidly, but when the dosage reaches 6g / L, the increase in the removal rate curve gradually slows down. At the same time, with the increase in the dosage of porous materials, the adsorption of ammonia nitrogen decreases rapidly before 4g / L, and the adsorption amount tends to be stable after 5g / L. Considering the economic cost and the effect of ammonia nitrogen adsorption, 4g / L is selected as the dosage for subsequent experiments.
[0041] The test was carried out under the condition that the amount of porous material was 4g / L. After characterization and analysis, the specific surface area of the prepared porous material reached 374.3m 2 / g, and the total pore volume is 0.2276cm 3 / g, and the ammonia nitrogen adsorption capacity is 15.9mg / g.
[0042] Example 2
[0043] The difference from Example 1 is that this embodiment adopts a drying temperature of 105°C for drying in the pretreatment stage, the mass fraction of hydrochloric acid used for pickling is 6%, and the pickling temperature is 80°C; in the alkali melting treatment stage, the mass ratio of sodium hydroxide to graphite tailings is 1.2:1, the calcination temperature is 700°C, and the calcination time is 1.5h; in the aging stage, the mass ratio of deionized water to alkali melt clinker is 6.25:1, and the stirring time is 6h; in the crystallization stage, the crystallization temperature is 80°C, and the crystallization time is 12h; in the last drying process before obtaining the graphite tailings porous material, the drying temperature is 105°C.
[0044] The test was carried out under the condition that the amount of porous material was 4g / L. After characterization and analysis, the specific surface area of the prepared porous material reached 375.9m 2 / g, and the total pore volume is 0.2306cm 3 / g, and the ammonia nitrogen adsorption capacity is 16.2mg / g.
[0045] Example 3
[0046] The difference from Example 1 is that this embodiment adopts a drying temperature of 103°C for drying in the pretreatment stage, the mass fraction of hydrochloric acid used for pickling is 10%, and the pickling temperature is 85°C; in the alkali melting treatment stage, the mass ratio of sodium hydroxide to graphite tailings is 1.5:1, the calcination temperature is 600°C, and the calcination time is 2h; in the aging stage, the mass ratio of deionized water to alkali melting clinker is 8:1, and the stirring time is 8h; in the crystallization stage, the crystallization temperature is 105°C, and the crystallization time is 24h; in the last drying process before obtaining the graphite tailings porous material, the drying temperature is 103°C.
[0047] The test was carried out under the condition that the amount of porous material was 4g / L. After characterization and analysis, the specific surface area of the prepared porous material reached 388.4m 2 / g, and the total pore volume is 0.3112cm 3 / g, and the ammonia nitrogen adsorption capacity is 17.4mg / g.
[0048] Example 4
[0049] The difference from Example 1 is that in this example, in the pretreatment stage, the mass fraction of hydrochloric acid used for pickling is 15%; in the alkali melting treatment stage, the calcination temperature is 800° C.; and in the aging stage, the stirring time is 12 h.
[0050] The test was carried out under the condition that the amount of porous material was 4g / L. After characterization and analysis, the specific surface area of the prepared porous material reached 372.8m 2 / g, and the total pore volume is 0.2215cm 3 / g, and the ammonia nitrogen adsorption capacity is 15.7mg / g.
[0051] Table 1 Reaction parameters and product statistics of Example 1-Example 4
[0052]
[0053] Table 1 (Continued) Reaction parameters and product statistics of Example 1-Example 4
[0054]
[0055]
[0056] As shown in Table 1, after testing, the specific surface area of the porous material products in each embodiment is higher than 370 m 2 / g, among which Example 3 has the highest specific surface area, with a specific surface area of 388.4m 2 / g, and the total pore volume is 0.3112cm 3 / g, and the ammonia nitrogen adsorption capacity is 17.4mg / g.
[0057] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for preparing a porous material based on graphite tailings, characterized in that: The graphite tailings are pretreated and alkali-melted, and then aged, crystallized and dried in sequence to obtain a graphite tailings porous material.
2. The method for preparing a porous material based on graphite tailings as claimed in claim 1, characterized in that: The pretreatment includes grinding and screening the graphite tailings raw material for the first time, and then drying it for the first time, mixing the dried product with hydrochloric acid, placing it in a reactor for pickling and impurity removal treatment, centrifuging the pickled sample, washing it with distilled water until the pH is neutral, centrifuging it again, drying the separated sample for the second time, and grinding and screening it for the second time for standby use.
3. The method for preparing a porous material based on graphite tailings as claimed in claim 2, characterized in that: The alkali melting treatment comprises uniformly mixing the pretreated graphite tailings, sodium hydroxide and aluminum hydroxide, placing the mixture into a high-temperature sintering furnace for calcining, and grinding the calcined sample to obtain alkali melting clinker.
4. The method for preparing a porous material based on graphite tailings as claimed in claim 2, characterized in that: The aging includes mixing deionized water with alkali-molten clinker and stirring at room temperature to form a precursor mixture.
5. The method for preparing porous material based on graphite tailings as claimed in claim 2, characterized in that: The crystallization comprises transferring the precursor mixture into a reaction kettle and sealing it, performing hydrothermal crystallization, cooling to room temperature after the crystallization is completed, and repeatedly washing the product with deionized water and centrifuging until the pH of the washing water is neutral.
6. The method for preparing porous materials based on graphite tailings as claimed in claim 2, characterized in that: In the pretreatment process, after the first grinding and screening and the second grinding and screening, raw materials with a particle size range of 200 mesh-300 mesh are selected for subsequent treatment, the drying temperature of the first drying and the second drying is 100-105°C, the mass fraction of hydrochloric acid in the pretreatment process is 3%-15%, and the temperature of the pickling and impurity removal is 70-85°C.
7. The method for preparing porous materials based on graphite tailings as claimed in claim 3, characterized in that: In the alkali melting treatment process, sodium hydroxide and graphite tailings are mixed at a mass ratio of 0.8-1.5:1, and the calcination temperature of the calcination process is 500-800° C. and the calcination time is 1-2 hours.
8. The method for preparing porous materials based on graphite tailings as claimed in claim 4, characterized in that: In the aging process, deionized water and alkali-molten clinker are mixed in a mass ratio of 4-8:1, the mass ratio of silicon to aluminum in the mixture is 1:1, and the stirring time is 2-12 hours.
9. The method for preparing a porous material based on graphite tailings as claimed in claim 5, characterized in that: The crystallization temperature of the crystallization process is 60-105° C., and the crystallization time is 4-24 hours.
10. The method for preparing porous materials based on graphite tailings according to claim 1, characterized in that: The last drying process before obtaining the graphite tailings porous material has a drying temperature of 100-105°C.
Citation Information
Patent Citations
Method for preparing porous materials with rare earth tailings
CN103896534A
Iron-tailing porous material as microbial ceramsite filtering material, preparation method of iron-tailing porous material and application of iron-tailing porous material
CN105693277A